Influence of recycled carbon fiber addition on the microstructure and creep response of extruded AZ91 magnesium alloy - Sinan Kandemir; Jan Bohlen; Hajo Dieringa (Journal of Magnesium and Alloys, 2023)
In this study, the recycled short carbon fiber (CF)-reinforced magnesium matrix composites were fabricated using a combination of stir casting and hot extrusion. The objective was to investigate the impact of CF content (2.5 and 5.0 wt.%) and fiber length (100 and 500 µm) on the microstructure, mechanical properties, and creep behavior of AZ91 alloy matrix. The microstructural analysis revealed that the CFs aligned in the extrusion direction resulted in grain and intermetallic refinement within the alloy. In comparison to the unreinforced AZ91 alloy, the composites with 2.5 wt.% CF exhibited an increase in hardness by 16–20% and yield strength by 5–15%, depending on the fiber length, while experiencing a reduction in ductility. When the reinforcement content was increased from 2.5 to 5.0 wt.%, strength values exhibited fluctuations and decline, accompanied by decreased ductility. These divergent outcomes were discussed in relation to fiber length, clustering tendency due to higher reinforcement content, and the presence of interfacial products with micro-cracks at the CF-matrix interface. Tensile creep tests indicated that CFs did not enhance the creep resistance of extruded AZ91 alloy, suggesting that grain boundary sliding is likely the dominant deformation mechanism during creep.